Administrative legal framework and organization of financial monitoring in the notary in Ukraine - Драна, Ірина Валентинівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article deals with issues of content and substance of administrative and legal support of financialmonitoring in the notary in Ukraine.